1991
DOI: 10.1002/j.1460-2075.1991.tb07656.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human PDGF-B gene is regulated by both positively and negatively acting cell type-specific regulatory elements located in the first intron.

Abstract: Potential cis‐acting regulatory elements of the human platelet derived growth factor‐B (PDGF‐B) gene were identified by DNase I hypersensitive site mapping. The transcription unit was examined for the presence of hypersensitive sites in chromatin DNA isolated from human term placental cytotrophoblasts, human placental fibroblasts, the JEG‐3 choriocarcinoma cell line and the U2‐OS osteosarcoma cell line. A number of cell type‐specific hypersensitive sites were identified, all within the 1st intron. Transient tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 33 publications
7
44
1
Order By: Relevance
“…DH sites at + 1.9 kb and + 4.0/+ 4.4 kb are especially pronounced in the placental cell lines. Recently, Franklin et al (1991) showed that a genomic fragment harbouring DH + 1.9, when cloned in the sense orientation upstream of the c-sis promoter, activates transcription fourfold in JEG-3 cells, while it reduces promoter activity 2-3-fold in U2-0s cells. Moreover, a fragment that contains DH + 4.0 appeared to activate the c-sis promoter 4-8-fold in JEG-3 and U2-0s cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DH sites at + 1.9 kb and + 4.0/+ 4.4 kb are especially pronounced in the placental cell lines. Recently, Franklin et al (1991) showed that a genomic fragment harbouring DH + 1.9, when cloned in the sense orientation upstream of the c-sis promoter, activates transcription fourfold in JEG-3 cells, while it reduces promoter activity 2-3-fold in U2-0s cells. Moreover, a fragment that contains DH + 4.0 appeared to activate the c-sis promoter 4-8-fold in JEG-3 and U2-0s cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reporter-gene studies showed that DNA elements within the first 100 bp upstream of the transcription-start site are important for phorbol-ester-mediated inducibility in vitro (Pech et al, 1989 b). Recently, DNase-Ihypersensitivity (DH) sites located in c-sis intron 1 of placental cytotrophoblasts were shown to enhance activity of the c-sis promoter in placental cells (Franklin et al, 1991).…”
mentioning
confidence: 99%
“…In previous studies transcription regulatory elements have been found in the c-sis promoter, exon 1, intron 1 and downstream of the gene (Pech et al, 1989b;Franklin et al, 1991 ;Dirks et al, 1993). Transcription regulatory elements located upstream of the c-sis promoter have not been found earlier.…”
mentioning
confidence: 89%
“…The JEG-3 choriocarcinoma cell line was maintained as has been described (Franklin et al, 1991). Subclones of the JEG-3 cell line were generated by transfecting a pSV2neo plasmid followed by neomycin selection as has been described (Franklin et al, 1991).…”
Section: Cell Samples and Preparation Of Nucleic Acidsmentioning
confidence: 99%
“…Subclones of the JEG-3 cell line were generated by transfecting a pSV2neo plasmid followed by neomycin selection as has been described (Franklin et al, 1991). Neomycin-resistant clones were isolated and expanded for 4 ± 5 passages before analysis.…”
Section: Cell Samples and Preparation Of Nucleic Acidsmentioning
confidence: 99%